Financial inclusion and nutrition among rural households in Rwanda - Ranjula Bali Swain; Aimable Nsabimana (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
We investigate if financial inclusion leads to improved nutrition in rural Rwanda, using Rwandan Integrated Household Living Conditions surveys (2013/14 and 2016/17). Our empirical evidence shows a robust positive impact of financial inclusion efforts undertaken by formal financial institutions, though informal institutions such as tontines are ineffective in improving food expenditure or nutrition. Furthermore, the study reveals heterogeneous marginal effects of financial inclusion in reducing the gender gap between the food demand and nutrition of femaleand male-headed households. The study provides suggestive evidence that promoting formal financial inclusion will lead to wide-ranging welfare effects by improving food security, nutrition, and food demand, especially in rural communities.
Keywords: D14; Q14; O16; 330; financial inclusion; food security; nutrition; Sustainable Development Goals; Rwanda